ANALISIS PUBLIC VALUE LAYANAN PANGGILAN KEGAWATDARURATAN BADAN NASIONAL PENCARIAN DAN PERTOLONGAN (BASARNAS) PADA KANTOR SAR SURABAYA - Ameilya Rizka Putri Prananda; Bagus Nuari Harmawan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the public value of the emergency call service provided by the National Search and Rescue Agency at the Surabaya SAR Office. The research is based on the importance of emergency services that are responsive, fast, and accessible to the public during disasters, accidents, and missing persons cases. As an institution responsible for search and rescue operations, Basarnas plays an important role in providing humanitarian assistance and ensuring public safety during emergency situations. Therefore, the quality of emergency call services becomes an essential aspect in supporting effective rescue operations and building public trust. This study employed a descriptive qualitative approach using interviews, observations, and documentation techniques to collect data from officers and related informants. The research applied the Public Value theory proposed by Faulkner and Kaufman(2018) (2017), which consists of Outcome Achievement, Trust and Legitimacy, Service Delivery Quality, and Efficiency. The findings show that the Basarnas emergency call service at the Surabaya SAR Office has been implemented effectively through successful rescue operations, responsive officers, and services that are easily accessed by the community. Public trust in the institution is also reflected in the positive perception of the officers’ professionalism and responsibility. In addition, the service is provided free of charge and supported by efficient resource utilization. However, continuous public outreach and the expansion of SAR operational coverage are still needed to improve service effectiveness in the future.